WORD EXPLORATION AND THE MEANING OF EVALUATION IN THE HOLY QURAN (THEMATIC INTERPRETATION OF EDUCATION EVALUATION) - Anwar Taufik Rakhmat; Ari Farizal Rasyid (Religio Education, 2021)
This study is intended to find the meaning of education evaluation in an Islamic perspective studied through the Holy Quran. By using a qualitative approach, content analysis research methods and data analysis techniques with the maudhui interpretation, it is found that the meaning of evaluation in the Holy Quran is found in words which mean evaluation in the form of terms derived from the words, حَسَبَ, نَظَرَ, بَلَا and اِمْتَحَنَ totaling 150 verses. Of the four words in the Holy Quran, the researcher defines educational evaluation as "a series of systematic and integrative activities in the educational process carried out by the evaluator (the subject of evaluation) to the evaluation (the object of evaluation) to obtain a description of the results of achievement and recommendations for the educational process undertaken." Its activities include data collection, data interpretation, and decision making.